PRAKTIK TAKHARRUJ WARIS DITINJAU DARI TEORI KEADILAN (Studi Kasus Masyarakat Desa Krecek Kecamatan Badas Kabupaten Kediri) - Kurnia Nisaul Khamidah (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
This study is motivated by the fact that the people of Krecek Village, Badas District, Kediri Regency, still uphold traditional and familial values in resolving inheritance disputes, including the practice of takharruj al-warits. This research employs a qualitative method by collecting field data. The primary data were obtained through interviews with individuals involved in takharruj al-warits practices in Krecek Village, while the secondary data consist of relevant publications and literature. Data analysis was carried out through data condensation, presentation, and verification. The results of this study show that: (1) The inheritance distribution in Krecek Village, Badas District, Kediri Regency uses the concept of takharruj, which emphasizes division through sulh (peaceful settlement). This occurs to maintain the integrity of family relations and solely for the benefit of the heirs. (2) from the perspective of John Rawls’ and Aristotle’s theories of justice, the inheritance distribution system in Krecek Village, in which one of the heirs withdraws due to economic considerations, can be considered justifiable since it is conducted through deliberation and mutual consent among the heirs; and (3) from the perspective of Islamic law, the practice of takharruj al-warits in Krecek Village may occur unilaterally, whereby an heir may relinquish their right to inheritance without requiring the consensus of other heirs, as long as it aims for maslahah (benefit) and does not contradict Sharia principles.